Tradisi Penyelenggaraan Aqiqah Masyarakat Kecamatan Kepenuhan - kamariah; ike betria; welven aida (Bakoba : Journal of Social Science Education, 2023)
That this research is based on the background of the problem of the tradition of holding aqiqah. The purpose of this study is to find out about the traditional procedures for carrying out aqiqah for the people of Kepuhan District. This research is a qualitative research using ethnographic methods. The subjects in this study were the Malay people of Kepuhan District. Informants in this study were traditional leaders, religious leaders, and the people of KeFullan District who knew about the tradition of holding aqiqah. Informant collection technique in this study is to use snowball sampling technique. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. The results of this study reveal that in the traditional way of holding aqiqah, the people of KeFullan District go through 8 stages. 1) Bopokat, 2) Adding a house 3) Making spices (grinding aweh), 4) slaughtering aqiqah animals, 5) marsanji, 6) cooking, 7) feasting (shaving children's hair, rubbing perfume, giving money, and inaugurating names children), 8) Wages.